Quantifying the social costs of pharmaceutical opioid misuse and illicit opioid use to Australia in 2015/16 - Makate, Marshall; Whetton, Steve; Tait, Robert; Chrzanowska, Agata; Donnelly, Neil; McEntee, Alice; Muhktar, Aqif; Zahra, Emma; Campbell, Gabrielle; Degenhardt, Louisa; Dey, Tania; Halim, Suraya Abdul; et al. (2020)
In recent decades the range and patterns of opioids used for extra-medical purposes have changed. The use of pharmaceutical opioids exceeds the use of heroin. In 2017, 63 percent of opioid deaths were attributed exclusively to pharmaceutical opioids, 28 percent to illicit opioids and 8 percent to both illicit and pharmaceutical opioids (aged 15-64 years).